2020
DOI: 10.17582/journal.aavs/2020/8.6.653.660
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Attenuates 6-Mercaptopurine Induced Testicular Toxicity in Albino Rats: Possible Mechanisms are Involved

Abstract: The present study was conducted in order to investigate the efficacy of thymoquinone (TQ) to attenuated 6-mercaptopurine (6MP) induced testicular toxicity with insight into the mechanism(s) of protection. 6MP is an anti-cancer and immunosuppressant chemotherapeutic drug; however, it had a potent toxic effect in various body organs. Forty male adult albino rats were allocated into four equal groups: control rats, TQ(5 mg/kg.BW orally) for a month, 6MP (5 mg/kg.BW orally) for twenty days, and TQ+6MP group pretre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…The current AZA-treated group revealed degenerated seminiferous tubules, marked decrease in spermatogenic cells, pyknotic nuclei, and vacuolated cytoplasm. The cytoplasmic vacuolation may be due to Sertoli cell damage since Sertoli cells control the spermatogenic process as explained in a recent research by Abdelbaky et al (2020). The present ultrastructural study of the MTX group revealed several extreme changes in spermatogonia and Sertoli cells.…”
Section: Discussionsupporting
confidence: 64%
“…The current AZA-treated group revealed degenerated seminiferous tubules, marked decrease in spermatogenic cells, pyknotic nuclei, and vacuolated cytoplasm. The cytoplasmic vacuolation may be due to Sertoli cell damage since Sertoli cells control the spermatogenic process as explained in a recent research by Abdelbaky et al (2020). The present ultrastructural study of the MTX group revealed several extreme changes in spermatogonia and Sertoli cells.…”
Section: Discussionsupporting
confidence: 64%
“…The current AZA-treated group revealed degenerated seminiferous tubules, marked decrease in the spermatogenic cells, pyknotic nuclei, and vacuolated cytoplasm. The cytoplasmic vacuolation may be due to Sertoli cell damage, where Sertoli cells control the spermatogenic process as explained by recent research byAbdelbaky et al (2020). The present ultrastructural study of the MTX group revealed several extreme changes in spermatogonia and Sertoli cells Richburg (2000),.…”
supporting
confidence: 64%
“…23 Researchers displayed beneficial effects of TQ to protect cells and tissues from standard chemotherapy-induced damages in in vivo animal models and in vitro human studies. 9,22,[24][25][26][27] Therefore, based on all this evidence, in the current study, the possible protective effect of TQ in two different dosages on BL-induced toxicity on male reproductive parameters was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…23 Researchers displayed beneficial effects of TQ to protect cells and tissues from standard chemotherapy-induced damages in in vivo animal models and in vitro human studies. 9,22,2427…”
Section: Introductionmentioning
confidence: 99%